Dynamic theory of condensed matters with internal structure - Kovalevsky, M.Yu.; Logvinova, L.V.; Matskevych, V.T. (Вопросы атомной науки и техники, 2007)
The results of investigations of condensed matters with internal structures are presented. Additional macroscopic parameters connected with this internal structure in the case of uniaxial and biaxial nematic liquid crystals and biological tissue are introduced as the definite functions of distortion tensor. Thermodynamics of such states is formulated and non-linear equations of hydrodynamics in alternating external field for these condensed matters are derived. Acoustic spectra of collective excitations are found out and their angular dependences are investigated. Low-frequency asymptotics of two-time Green functions are obtained.